Analisis Faktor Keluarga yang Berkontribusi terhadap Hambatan Emosi dan Perilaku pada Remaja Binaan di Lapas Kelas IIA Metro Lampung - Ratna Tri Utami; Muhammad Ubaidillah (Jurnal Pendidikan Kebutuhan Khusus, 2026)
Emotional and behavioral disorders among adolescents in conflict with the law are influenced by various interrelated factors. This study aimed to analyze family-related factors contributing to emotional and behavioral disorders among juvenile inmates at the Class IIA Metro Correctional Institution, Lampung. This study employed a descriptive qualitative approach. The participants consisted of six juvenile inmates, two correctional officers, and one parent selected through purposive sampling. Data were collected through in-depth interviews focusing on family conditions and parenting styles, observations of social behavior, emotional regulation, and interactions during rehabilitation activities, as well as documentation of identity records, educational histories, and juvenile rehabilitation records. The findings revealed that family factors were the dominant cause of emotional and behavioral disorders among juvenile inmates. The main findings included parental divorce and family disharmony, economic pressures that limited parental involvement in child-rearing, and permissive parenting characterized by inadequate supervision of children’s behaviour. These findings highlight the importance of strengthening family functioning as a preventive strategy to minimize emotional and behavioral disorders among adolescents.